Location versus ID: what matters to lung-resident memory T cells? - Macedo, Bruna Gois; Masuda, Mia Y.; Borges da Silva, Henrique (Frontiers in Immunology, 2024)
Tissue-resident memory T cells (TRM cells) are vital for the promotion of barrier immunity. The lung, a tissue constantly exposed to foreign pathogenic or non-pathogenic antigens, is not devoid of these cells. Lung TRM cells have been considered major players in either the protection against respiratory viral infections or the pathogenesis of lung allergies.Establishment of lung TRM cells rely on intrinsic and extrinsic factors. Among the extrinsic regulators of lung TRM cells, the magnitude of the impact of factors such as the route of antigen entry or the antigen natural tropism for the lung is not entirely clear. In this perspective, we provide a summary of the literature covering this subject and present some preliminary results on this potential dichotomy between antigen location versus antigen type. Finally, we propose a hypothesis to synthesize the potential contributions of these two variables for lung TRM cell development.